Analysis of Caffeine Content of Liberica Coffee (Coffea liberica) with Variations of Roasting Methods at Kalipuro Research Center, Banyuwangi District - Almayda, Nabila; Najih, Riyan Riyadlun (Directorate of Research and Community Services, 2024)
The roasting process is one of the keys in the coffee production stage. Roasting affects the quality of coffee in terms of organoleptic characteristics.This study aims to analyze the chemical content of liberica coffee. The research was carried out at the Kalipuro Research Institute (Kembang Galengan) using two types of roasting methods, namely conventional and modern (machine-roasted). Testing of liberica coffee samples by analyzing water content, ash content, acidity levels (pH), and caffeine. The results showed that modern coffee roasting produces a water content of 4%, ash content of 5.1%, acidity (pH) of 4.7, and caffeine content of 0.47%. Meanwhile, conventional roasting produces a water content of 2.5%, ash content of 4.9%, acidity (pH) of 4.7%, and caffeine content of 0.28%. Based on these results, it can be concluded that all categories of liberica coffee processed conventionally and modernly (machine-roasted) at the Kalipuro Research and Development Center qualify for SNI standards.